(2x+7)(x-3)(x+3)(2x+5)=91

Simple and best practice solution for (2x+7)(x-3)(x+3)(2x+5)=91 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+7)(x-3)(x+3)(2x+5)=91 equation:


Simplifying
(2x + 7)(x + -3)(x + 3)(2x + 5) = 91

Reorder the terms:
(7 + 2x)(x + -3)(x + 3)(2x + 5) = 91

Reorder the terms:
(7 + 2x)(-3 + x)(x + 3)(2x + 5) = 91

Reorder the terms:
(7 + 2x)(-3 + x)(3 + x)(2x + 5) = 91

Reorder the terms:
(7 + 2x)(-3 + x)(3 + x)(5 + 2x) = 91

Multiply (7 + 2x) * (-3 + x)
(7(-3 + x) + 2x * (-3 + x))(3 + x)(5 + 2x) = 91
((-3 * 7 + x * 7) + 2x * (-3 + x))(3 + x)(5 + 2x) = 91
((-21 + 7x) + 2x * (-3 + x))(3 + x)(5 + 2x) = 91
(-21 + 7x + (-3 * 2x + x * 2x))(3 + x)(5 + 2x) = 91
(-21 + 7x + (-6x + 2x2))(3 + x)(5 + 2x) = 91

Combine like terms: 7x + -6x = 1x
(-21 + 1x + 2x2)(3 + x)(5 + 2x) = 91

Multiply (-21 + 1x + 2x2) * (3 + x)
(-21(3 + x) + 1x * (3 + x) + 2x2 * (3 + x))(5 + 2x) = 91
((3 * -21 + x * -21) + 1x * (3 + x) + 2x2 * (3 + x))(5 + 2x) = 91
((-63 + -21x) + 1x * (3 + x) + 2x2 * (3 + x))(5 + 2x) = 91
(-63 + -21x + (3 * 1x + x * 1x) + 2x2 * (3 + x))(5 + 2x) = 91
(-63 + -21x + (3x + 1x2) + 2x2 * (3 + x))(5 + 2x) = 91
(-63 + -21x + 3x + 1x2 + (3 * 2x2 + x * 2x2))(5 + 2x) = 91
(-63 + -21x + 3x + 1x2 + (6x2 + 2x3))(5 + 2x) = 91

Combine like terms: -21x + 3x = -18x
(-63 + -18x + 1x2 + 6x2 + 2x3)(5 + 2x) = 91

Combine like terms: 1x2 + 6x2 = 7x2
(-63 + -18x + 7x2 + 2x3)(5 + 2x) = 91

Multiply (-63 + -18x + 7x2 + 2x3) * (5 + 2x)
(-63(5 + 2x) + -18x * (5 + 2x) + 7x2 * (5 + 2x) + 2x3 * (5 + 2x)) = 91
((5 * -63 + 2x * -63) + -18x * (5 + 2x) + 7x2 * (5 + 2x) + 2x3 * (5 + 2x)) = 91
((-315 + -126x) + -18x * (5 + 2x) + 7x2 * (5 + 2x) + 2x3 * (5 + 2x)) = 91
(-315 + -126x + (5 * -18x + 2x * -18x) + 7x2 * (5 + 2x) + 2x3 * (5 + 2x)) = 91
(-315 + -126x + (-90x + -36x2) + 7x2 * (5 + 2x) + 2x3 * (5 + 2x)) = 91
(-315 + -126x + -90x + -36x2 + (5 * 7x2 + 2x * 7x2) + 2x3 * (5 + 2x)) = 91
(-315 + -126x + -90x + -36x2 + (35x2 + 14x3) + 2x3 * (5 + 2x)) = 91
(-315 + -126x + -90x + -36x2 + 35x2 + 14x3 + (5 * 2x3 + 2x * 2x3)) = 91
(-315 + -126x + -90x + -36x2 + 35x2 + 14x3 + (10x3 + 4x4)) = 91

Combine like terms: -126x + -90x = -216x
(-315 + -216x + -36x2 + 35x2 + 14x3 + 10x3 + 4x4) = 91

Combine like terms: -36x2 + 35x2 = -1x2
(-315 + -216x + -1x2 + 14x3 + 10x3 + 4x4) = 91

Combine like terms: 14x3 + 10x3 = 24x3
(-315 + -216x + -1x2 + 24x3 + 4x4) = 91

Solving
-315 + -216x + -1x2 + 24x3 + 4x4 = 91

Solving for variable 'x'.

Reorder the terms:
-315 + -91 + -216x + -1x2 + 24x3 + 4x4 = 91 + -91

Combine like terms: -315 + -91 = -406
-406 + -216x + -1x2 + 24x3 + 4x4 = 91 + -91

Combine like terms: 91 + -91 = 0
-406 + -216x + -1x2 + 24x3 + 4x4 = 0

The solution to this equation could not be determined.

See similar equations:

| X^3-7x+y=1 | | 33.000/00 | | (8x+1)=(15x+10) | | 5x+1y+.05z=100 | | 2x=33-4x | | 2n+3+5+7= | | 400+x=977 | | 30x+20y=5930 | | log2/log1.15 | | x(x-4)-4=0 | | an=n-3 | | 600=.30x | | 8=2k+2k | | 299=332-x | | 3x+18+2y=0 | | 813/4= | | 8x=-46 | | 121=73+x | | 10=0.82x | | 127-x=54 | | h(t)=-4.9t^2+5.9t+2 | | 13+19=z+5 | | 2x+24y=x | | p=-3+5c | | 3/5m=-8/7 | | 16=6+c | | e-5=17+3 | | 17p+12=10p-13 | | 5*5*5=/=500 | | X+77=81 | | 5*5*5=500 | | 12=x/12 |

Equations solver categories